Konsep Pengembangan Sumber Daya Manusia Berbasis Kompetensi, Bakat dan Ketahanan dalam Organisasi - Yostan A Labola (University of Merdeka Malang, 2019)
Many companies have poor performance because they don’t have human resources relevated with their needs. Some of those organizations will not survive for long term in business competition. In this case Human Resource Development (HR) becomes a fundamental parameter for the success and achievement of organizational goals in order to exist. Based on literature review, the concept of developing an HR organization needs to pay attention on aspects of competence, talent, and resilience of employees. The competency aspect is the potential long-term value and potential source of the company's competitive advantage. While the talent aspect becomes a critical point for the company for the positions needed, and with the toughness aspect, employees are able to face competition and overcome difficulties to become opportunities for greater achievement. Thus, the vision, mission and expectations of the organization can lead to success.https://doi.org/10.26905/jmdk.v7i1.2760